2020
DOI: 10.1101/2020.01.11.902981
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Recognition of cellular RNAs by the S9.6 antibody creates pervasive artefacts when imaging RNA:DNA hybrids

Abstract: The contribution of RNA:DNA hybrid metabolism to cellular processes and disease states has become a prominent topic of study. The S9.6 antibody recognizes RNA:DNA hybrids with a subnanomolar affinity, making it a broadly used tool to detect and study RNA:DNA hybrids. However, S9.6 also binds double-stranded RNA in vitro with significant affinity. Though frequently used in immunofluorescence microscopy, the possible reactivity of S9.6 with non-RNA:DNA hybrid substrates in situ, particularly RNA, has not been co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 52 publications
2
10
0
Order By: Relevance
“…While RNA:DNA hybrids are expected to show an exclusively nuclear and mitochondrial (as well as—in plants—chloroplastic) distribution, most studies report that the majority of the IF signals detected by S9.6 antibodies is cytoplasmic. Recent results (preprint: Smolka et al , 2020) show that, under normal conditions in human cells, the S9.6 signal does not overlap with mitochondria, in agreement with prior work (Koo et al , 2015; Silva et al , 2018). In addition, this cytoplasmic signal was found not to be sensitive to exogenous RNase H treatment (Silva et al , 2018; preprint: Smolka et al , 2020), even under conditions where RNase H was proven effective against transfected in vitro labeled RNA:DNA hybrids (preprint: Smolka et al , 2020).…”
Section: Introductionsupporting
confidence: 86%
See 2 more Smart Citations
“…While RNA:DNA hybrids are expected to show an exclusively nuclear and mitochondrial (as well as—in plants—chloroplastic) distribution, most studies report that the majority of the IF signals detected by S9.6 antibodies is cytoplasmic. Recent results (preprint: Smolka et al , 2020) show that, under normal conditions in human cells, the S9.6 signal does not overlap with mitochondria, in agreement with prior work (Koo et al , 2015; Silva et al , 2018). In addition, this cytoplasmic signal was found not to be sensitive to exogenous RNase H treatment (Silva et al , 2018; preprint: Smolka et al , 2020), even under conditions where RNase H was proven effective against transfected in vitro labeled RNA:DNA hybrids (preprint: Smolka et al , 2020).…”
Section: Introductionsupporting
confidence: 86%
“…In addition, this cytoplasmic signal was found not to be sensitive to exogenous RNase H treatment (Silva et al , 2018; preprint: Smolka et al , 2020), even under conditions where RNase H was proven effective against transfected in vitro labeled RNA:DNA hybrids (preprint: Smolka et al , 2020). Instead, the sensitivity of the cytoplasmic signal to RNA‐specific ribonucleases T1 and III implicated that the majority of the S9.6 signal in standard IF microscopy studies derives from RNA, but not from RNA:DNA hybrids (Silva et al , 2018; preprint: Smolka et al , 2020). These observations do raise substantive concerns about the results of past S9.6‐based imaging studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings contrast with previous studies which reported that PladB and other splicing inhibitors caused broad R-loops gains (Nguyen et al, 2018;Nguyen et al, 2017;Wan et al, 2015). Such claims, however, relied on S9.6-based imaging approaches which are unreliable without proper controls due to the affinity of the S9.6 antibody for structured RNAs (Hartono et al, 2018;Phillips et al, 2013;Smolka et al, 2020). The observations that PladB treatment triggers a broad enlargement of RNA-rich nuclear speckles (Effenberger et al, 2014) suggests that RNA distribution is profoundly altered, further raising the possibility of significant imaging artefacts.…”
Section: Sf3b1-mediated Splicing Inhibition Triggers Global Promoter-mentioning
confidence: 99%
“…Mapping and all downstream analysis was performed on two independent biological replicates. R-loops were also mapped using sDRIP-seq, a variant of DRIP-seq that permits strand-specific R-loop mapping after genome fragmentation using sonication (Smolka et al, 2020).…”
Section: Analysis Of R-loop Genomic Distribution By Drip-seq and Dripmentioning
confidence: 99%